(untitled) (Global Journal of Science Frontier Research, 2023)
This paper proposes an interesting representation VCKM qRGB of Cabibbo-Kobayashi-Maskawa Matrix CKM which based on scalar products of quark color quantum numbers qR qG qB or qRGB 00 1 This representation is called colorization of CKM in weak interaction The colors of down-type quarks qw w d s b in the quarkcolor scalar products of CKM are Color-Broken 0 which results in isospin I3 qw to be violated in weak interaction further charges Qdsb CKM rw to be a slight deviated from 1 3 e of SM theoretical value A short discussion of possible existence of higher-charges of quark q is given in Epilogue